Fruit Farming and Tribal Autonomy in Oklahoma’s Green Country: A Native American Business Model - Altamirano, Janet Lynne (Advances in Social Sciences Research Journal, 2018)
An exploration of a Native American business model used by the Cherokee and Muscogee (Creek) Indian tribes. Key words: Economic development, Native American economy